Productive potential of cucumber fruits (Cucumis sativus L.) for preservation under different driving (Research, Society and Development, 2022)
In order to evaluate the potential of cucumber production for canning, an entirely randomized design experiment was conducted with three cultivars and two managements, adopting four repetitions. The plots were distributed in four planting lines, via direct sowing, with 1.50 m x 0.45 m spacing between plants. Two managements were adopted: management 1) without sprouting and apical pruning; management 2) with sprouting and apical pruning. After 70 days of planting, total fresh mass of fruits per plant, average number of fruits per plant and productivity were evaluated. Among the cultivars, Marinda and Amour F1 stood out for handling 1, with total fresh mass yields of 1762.75 g and 1026.71 g respectively, and 135.69 and 79.62 average number of fruits per plant. In handling 2, the cultivars Marinda and Eureka obtained better yields, with a total fresh mass of 1966,94 g and 1605,31 g respectively, and 146,17 and 90,09 average number of fruits per plant. The cultivar Marinda both for handling 1 and handling 2 obtained the best yield.  Among the tested cultivars, the cultivation of Marinda and Eureka cultivars associated to apical pruning and capation is suggested.